Application Of Psak 10 Concerning The Presentation Of Financial Statements On Foreign Exchange Transactions To The Financial Statements Of Pt Alumino Light Meta Industry, Tbk. - Sukma Ayu Mustika (Business Finence Analyst Co.,, 2025)
The application of the Financial Accounting Standards Statement (PSAK) 10 has become very relevant in managing foreign exchange transactions, especially for companies that are active in international trade. This study aims to analyze the application of PSAK 10 at PT Alumino Light Meta Industry Tbk, with a focus on the impact of exchange rate fluctuations on the company's financial statements. The research approach uses a mixed-method method that includes qualitative analysis to understand the process of implementing PSAK 10 and quantitative analysis to evaluate its impact on financial statements for the 2019-2023 period. The results of the study show that PT Alumino consistently recognizes foreign exchange transactions based on the prevailing exchange rate at the time the transaction occurs, as well as recording the exchange rate difference as profit or loss. The implementation of PSAK 10 has had a significant impact on the income statement and other comprehensive income, although the company's overall performance has tended to decline over the past five years. This study emphasizes the importance of implementing PSAK 10 in creating accurate and transparent financial reports, as well as managing the risk of foreign exchange rate fluctuations. This study recommends further studies on foreign exchange risk mitigation strategies, such as hedging, as well as an analysis of the implementation of PSAK 10 in various industrial sectors. Keywords: PSAK 10, foreign exchange transactions, exchange rate differences, financial statements